EDUKASI KESEHATAN DASAR PANGGUL DAN LATIHAN KEGEL BAGI IBU HAMIL: PROGRAM KEMITRAAN MASYARAKAT - Kurniawati, Eighty Mardiyan; Hardianto, Gatut; Wahyuningtyas, Riska; Rahmawati, Nur Anisah; Mustofa, Vina Firmanty; Safitri, Cahyani Tiara; Kurniawan, Agde Muzaky; Mardianti, Mardianti (Jurnal AbdiMas Nusa Mandiri, 2025)
Cesarean delivery is associated with complications in pregnant women, including pelvic floor disorders. Kegel exercises can help maintain pelvic floor health and support normal delivery. This community service activity aimed to provide education on pelvic floor health and Kegel exercises to empower pregnant women at Pucang Sewu Public Health Center, Surabaya, in 2024. The program was conducted in three stages: preparation, implementation, and evaluation. Preparation involved coordination, planning, and developing a physical activity book for pregnant women. The implementation phase included education sessions and Kegel exercise training using a two-way communication method. Evaluation was conducted through pretest–posttest and observation of participants’ practice skills. The activity was attended by 27 pregnant women and 10 healthcare workers. The results showed increased knowledge and skills among participants after the training, indicated by higher posttest scores and active participation during practice. More than half of the participants had never exercised regularly before. This program effectively improved participants’ understanding and ability to perform Kegel exercises. The health center is expected to continue providing education to encourage pregnant women to practice Kegel exercises independently at home.